2018
DOI: 10.3390/w10040356
|View full text |Cite
|
Sign up to set email alerts
|

Crop Upgrading Strategies and Modelling for Rainfed Cereals in a Semi-Arid Climate—A Review

Abstract: Spatiotemporal rainfall variability and low soil fertility are the primary crop production challenges facing poor farmers in semi-arid environments. However, there are few solutions for addressing these challenges. The literature provides several crop upgrading strategies (UPS) for improving crop yields, and biophysical models are used to simulate these strategies. However, the suitability of UPS is limited by systemization of their areas of application and the need to cope with the challenges faced by poor fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 165 publications
1
19
0
Order By: Relevance
“…The conclusion drawn by Silungwe et al [25] from the examined literature was that the most suitable models to simulate the considered UPS were the Decision Support System for Agrotechnology Transfer (DSSAT), the Agricultural Production Systems Simulator (APSIM), and the AquaCrop model. Bell et al [17] found that farmer decisions in Malawi followed a dynamic of peer influence, with neighbors' adoption as the most effective factor.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The conclusion drawn by Silungwe et al [25] from the examined literature was that the most suitable models to simulate the considered UPS were the Decision Support System for Agrotechnology Transfer (DSSAT), the Agricultural Production Systems Simulator (APSIM), and the AquaCrop model. Bell et al [17] found that farmer decisions in Malawi followed a dynamic of peer influence, with neighbors' adoption as the most effective factor.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Akramkhanov et al [28] involved local stakeholders in Uzbekistan in a transdisciplinary and participatory approach for innovation development. From a methodological point of view, the contributions involve both field [15,16,18,23,24,29] and laboratory [19] experiments, and modeling [20][21][22], survey [17,27,28] and review [25] studies. The Special Issue includes studies carried out at different spatial scales, from field-to regional-scales.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations